2012
DOI: 10.1016/j.ijgo.2011.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Placental mRNA in maternal plasma as a predictor of ectopic pregnancy

Abstract: Objective To measure and compare placental mRNA expression in the maternal circulation among women with intrauterine and ectopic pregnancies. Methods Plasma was collected from patients in early pregnancy at risk of ectopic pregnancy. Clinical information was prospectively collected and entered into a dedicated database. mRNA was isolated from maternal plasma and quantitative RT-PCR was performed to measure mRNA for human gonadotropin (hCG) and human placental lactogen (hPL). GAPDH mRNA expression was used as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 18 publications
0
6
1
Order By: Relevance
“…These potential proteins include, but are not limited to: Inhibin A, which is produced by the corpus luteum; activin A, pregnancy-associated plasma protein-A (PAPP-A) and A Disintegrin and Metalloprotease-12 (ADAM-12) which are generated by the placenta; and vascular endothelial growth factor (VEGF), which, produced by a variety of cell types, is crucial for angiogenesis and may be upregulated in EP [ 75 ]. Various messenger and micro-RNA—regulators of downstream gene expression—may also be differentially expressed by an EP [ 81 , 82 ].…”
Section: Reviewmentioning
confidence: 99%
“…These potential proteins include, but are not limited to: Inhibin A, which is produced by the corpus luteum; activin A, pregnancy-associated plasma protein-A (PAPP-A) and A Disintegrin and Metalloprotease-12 (ADAM-12) which are generated by the placenta; and vascular endothelial growth factor (VEGF), which, produced by a variety of cell types, is crucial for angiogenesis and may be upregulated in EP [ 75 ]. Various messenger and micro-RNA—regulators of downstream gene expression—may also be differentially expressed by an EP [ 81 , 82 ].…”
Section: Reviewmentioning
confidence: 99%
“…Serum human chorionic gonadotrophin (HCG) levels are often used to discriminate between intra‐uterine and ectopic pregnancies but are poor predictors of outcome. Takacs et al found that circulating HPL and HCG RNA were significantly lower or undetectable in ectopic compared with intra‐uterine pregnancies, allowing earlier discrimination and, therefore, intervention . In intra‐uterine pregnancies, Farina et al also noted lower levels of placental‐specific 1 gene in pregnancies complicated by vaginal bleeding compared with healthy controls, although this did not predict miscarriage .…”
Section: Biomarkers For Placental and Fetal Healthmentioning
confidence: 99%
“…Placental mRNAs secreted by trophoblasts can be altered in early pregnancy failure, and therefore have been studied recently for their diagnostic potential in EP. A recent case-control study conducted by Takacs et al demonstrated that patients with EP have significantly lower copy numbers of hCG and hPL mRNA in plasma compared to viable IUP [54]. Placental mRNA have also been studied for viability and chromosomal aneuploidy [55,56].…”
Section: Placental Mrnamentioning
confidence: 99%